What Team Science leaders really want: leveraging the knowledge of CTSA-based Team Science leaders to advance the Science of Team Science - Rolland, Betsy; Glauber, Kristine M.; McCormack, Wayne T.; Wooten, Kevin; Risser, Heather J.; Brasier, Allan R. (Frontiers in Psychology, 2026)
Clinical and Translational Science Award (CTSA) hubs invest substantial resources in facilitating a Team Science approach to research. Despite over 15 years of Science of Team Science research, the field lacks evidence-based interventions that can be implemented by CTSA hubs and others in support of collaborative research. Federal funding agencies increasingly call for team-based research but devote few resources to the development, dissemination, and evaluation of Team Science interventions. This lack of feasible interventions leaves CTSA Team Science leaders and Clinical and Translational Research Teams (CTRTs) themselves with few evidence-based options for improving the impact of team-based research. In this project, a group of CTSA Team Science leaders conducted a pilot study to understand this gap better. First, we engaged in a semi-structured needs assessment to answer two questions: (1) What do CTRTs need to thrive in conducting team-based Clinical and Translational Research, and (2) What do CTSA-based Team Science leaders need to build robust Team Science programs that serve CTRTs? Second, we conducted a landscape assessment to identify existing evidence-informed team-based interventions. Third, we designed and launched a hybrid effectiveness-feasibility project. Here, we report on these three activities. Finally, we call for additional funding to support the development, dissemination, and evaluation of these critical interventions.